Performance Analysis of Bio-batteries from Organic Waste for Alternative Electric Energy - M. Arya Nata Raharjo; Amanda Fajar Arifia; Kartini Herlina (CV Media Inti Teknologi, 2025)
Background of study: Biobatteries are an innovative form of renewable energy technology that utilize organic materials to produce electricity through electrochemical reactions. Organic waste such as banana and pineapple peels contains natural electrolytes, making them potential sustainable and eco-friendly energy sources.Aims and scope of paper: This study aims to evaluate the performance of simple biobatteries using banana and pineapple peels as electrolyte materials. The research focuses on measuring voltage and current generation over seven days and assessing the stability and durability of each type of organic waste.Methods: Biobatteries were assembled using zinc (Zn) electrodes as the anode and carbon rods as the cathode. The peels were ground into a paste and used as the electrolyte. Daily measurements of voltage and current were taken for seven consecutive days to analyze performance trends.Result: Test results showed that both types of biobatteries were capable of producing sufficient voltage and current to power simple electronic devices such as small LEDs, wall clocks, and basic household appliances. However, biobattery performance decreased over time due to water evaporation, degradation of active compounds, and environmental influences such as temperature and humidity. Overall, banana peels performed more consistently than pineapple peels.Conclusion: This research demonstrates that organic waste can serve as a viable material for renewable energy generation. Biobatteries made from fruit peels not only help reduce waste but also have potential for educational use and community energy initiatives.